Use of Different Methods in English Lessons - Shodiev Miryoqub; Bafoev Farrukh (Open Academia, 2023)
This article describes the use of different methods in English language classes , the fact that diagnostic methods aimed at learning the innovative activities of the teacher are also diverse , and that arming future teachers with modern methods of diagnosis is the demand of the times. given information
Keywords: Diagnostic methods; methodological; innovative; pedagogue